2020
DOI: 10.1080/24733938.2020.1799064
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fatigue on first stance phase kinetics during acceleration sprint running in professional football players

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The results of this study contrast with previous research on repeated sprint training performed with unresisted sprints. Prior studies have shown that during repeated sprints, fatigue leads to greater decreases in force and power output in the first and later phases of sprinting [24,33,[72][73][74]. Sustaining sprints with reduced force and power applied by the neuromuscular system makes it difficult to achieve positive adaptations on maximal and repeated sprint ability for soccer players [75].…”
Section: Resisted Sprint Performance and Mechanical Variablesmentioning
confidence: 99%
“…The results of this study contrast with previous research on repeated sprint training performed with unresisted sprints. Prior studies have shown that during repeated sprints, fatigue leads to greater decreases in force and power output in the first and later phases of sprinting [24,33,[72][73][74]. Sustaining sprints with reduced force and power applied by the neuromuscular system makes it difficult to achieve positive adaptations on maximal and repeated sprint ability for soccer players [75].…”
Section: Resisted Sprint Performance and Mechanical Variablesmentioning
confidence: 99%